Peran Partisipasi Masyarakat Dalam Pendidikan Di Kawasan RT. 30 Sangatta Utara - Hidayah, Nur Fitri; Sairah, Nor; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
Community participation Refers to the involvement of individuals in activities or processes that influence life together in a community or society. This can include a variety of things, from political participation to participation in social organizations, volunteer activities, education, and more. This research uses a qualitative approach. Data collection uses observation, interviews and documentation. The research was conducted with the aim of finding out what role educational participation plays in society? What are the forms of community participation in educational development in the RT. 30 community area? The role of community participation and schools is required to work together effectively to improve educational standards. For the sake of progress and education of students, schools and communities are also expected to share information, ideas and opinions. because it is becoming more advanced due to advances in science and forms of participation in the form of holding meetings, before announcing the amount of the committee fee, the school will usually hold a parent meeting, socialization between teachers and parents of students and is usually led directly by the head of the community. Forms of Community Participation in the Development of Education in the RT. 30 Community Area Apart from the government, parents and the community also have a responsibility to educate their children.